The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1151-2916.2002.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Atmosphere on Grain Boundary Segregation and Grain Growth in Niobium‐Doped SrTiO3

Abstract: To investigate the donor segregation in grain boundary regions and its effect on grain growth in SrTiO3, SrTiO3 powder compacts were doped with Nb2O5 and sintered in air or in hydrogen. The Nb‐doped SrTiO3 sintered in air did not show any detectable Nb segregation at the grain boundary region while an appreciable segregation was observed in the space‐charge region of the sample sintered in H2. The observed donor segregation in H2 suggests a negative grain boundary charge and compensating positive space charge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 54 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…Similar lithium insertion experiments on perovskite structured materials, with Ti and Nb on the B-site, have suggested analogous results [38]. Xray photoelectron spectroscopy (XPS) on Nb-doped SrTiO 3 has also confirmed that the valance state of Nb is +V, even after sintering at 1360°C in highly reducing atmospheres (dry H 2 ) [39].…”
Section: Phase Characterization and Defect Structurementioning
confidence: 71%
“…Similar lithium insertion experiments on perovskite structured materials, with Ti and Nb on the B-site, have suggested analogous results [38]. Xray photoelectron spectroscopy (XPS) on Nb-doped SrTiO 3 has also confirmed that the valance state of Nb is +V, even after sintering at 1360°C in highly reducing atmospheres (dry H 2 ) [39].…”
Section: Phase Characterization and Defect Structurementioning
confidence: 71%
“…It has been reported by Chung et al [24] that sintering atmosphere influences the grain growth behaviour of donor doped BaTiO 3 . A reducing atmosphere is conducive to grain growth due to increase in oxygen vacancies concentration.…”
Section: Resultsmentioning
confidence: 96%
“…The grain boundaries of strontium titanate are charged [56,57] and different intrinsic [21] or extrinsic [56][57][58] defects segregate or are depleted. The content of extrinsic defects ('solutes') is very low in the ceramic powder used in the current study [42].…”
Section: Drag Effects On Grain Growthmentioning
confidence: 99%